EHSAAS EMERGENCY CASH PROGRAM: A STEP TOWARDS WOMEN EMPOWERMENT IN PAKISTAN - Rashida Amin; Hafsa Shamoon; Sehar Mubeen; Maleeha Adil (International Journal of Contemporary Issues in Social Sciences, 2023)
The main aim of this paper is to highlight the effect of Ehsaas emergency cash program on poverty. Actually, this is a step towards women empowerment in Pakistan. Due to COVID-19, a sudden lockdown was imposed on people. people have nothing to eat they were living in very sensitive condition. Government take a serious step, Ehsaas program was started, through this some amount of cash was transferred to women account. Through this financial state of people were improved. Poverty is the major problem in our society and due to this fact woman are suffering more in the society. They were not able to contribute in improving the financial condition of houses. They do not have any resource through which they maintain their household income. Ehsaas emergency cash program was a step to reduce poverty. women are able to contribute in improving their home condition. This micro credit helps them to enjoy a good status. Through this some burden was reduced from their life. Financial state of people was improved. It empowering the poorer sectors of the society and also increasing their living standards. Women gain their rights and also stands with their family at this difficult time. Women considered this program to much beneficiary for them. This program helps them to reduce their poverty. Through this condition of society goes towards best. Now Ehsaas program is considered Pakistan’s greatest social protection initiative programmed. Sustainable development is achieved through it.